2021
DOI: 10.1155/2021/3459401
|View full text |Cite
|
Sign up to set email alerts
|

The Transmutation Logic of China University Science and Technology Innovation System since the Founding of the Communist Party of China One Hundred Years Ago: Three-Chain Perspectives Led by Party-Building

Abstract: The university science and technology innovation system is an essential bridge between higher education and national innovation development. Since the founding of the Communist Party of China, the scientific and technological innovation system of Chinese universities has intermingled with the historical environment and internal and external factors and has gone through several stages of development from weak to strong and from fragile to solid. In this process, the Communist Party of China has always been firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Asia-specific empirical data demonstrate that financial inclusion and development may certainly support sustainable natural resource management. For instance, research by Liu et al (2021) found that smallholder farmers in Nepal adopted sustainable land management methods at a much higher rate when they had access to loans (Liu, Khan, et al, 2022). Research indicated that having access to microfinance services encouraged rural Indian families to invest in clean energy technology.…”
mentioning
confidence: 99%
“…Asia-specific empirical data demonstrate that financial inclusion and development may certainly support sustainable natural resource management. For instance, research by Liu et al (2021) found that smallholder farmers in Nepal adopted sustainable land management methods at a much higher rate when they had access to loans (Liu, Khan, et al, 2022). Research indicated that having access to microfinance services encouraged rural Indian families to invest in clean energy technology.…”
mentioning
confidence: 99%
“…Any time-related variable or trend might be represented using it Assuming that all other variables remain constant, the coefficient _1 for T_t shows the change in Y_t for a one-unit change in T_t. Another independent variable, D_t, indicates the existence or absence of a particular ailment or course of therapy ( Liu et al, 2021 ). It could be a binary variable, such as a dummy variable that denotes whether an event or a policy is being implemented.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion of science and technology-related modules in the Mainland China curriculum aligns with China's "Revitalizing the Nation through Science and Education" initiative, first introduced in the "Decision on Accelerating Scientific and Technological Progress" issued by the Central Committee and the State Council of the Chinese Communist Party in 1995 (Liu et al, 2021). Furthermore, it reflects China's tradition of emphasizing history and politics due to its extensive cultural heritage and political traditions (Lu & Yan, 2022).…”
Section: Technementioning
confidence: 99%